Selective laser melting of nano-TiB2 decorated AlSi10Mg alloy with high fracture strength and ductility. (1st May 2017) - Li, X.P.; Ji, G.; Chen, Z.; Addad, A.; Wu, Y.; Wang, H.W.; Vleugels, J.; Van Humbeeck, J.; Kruth, J.P.
Abstract: An in-situ nano-TiB2 decorated AlSi10Mg composite (NTD-Al) powder was fabricated by gas-atomisation for selective laser melting (SLM). Fully dense and crack-free NTD-Al samples were produced using SLM. In contrast to the NTD-Al powder without cell-like microstructure, the SLMed NTD-Al had a textureless microstructure, consisting of fine grains and cells, with well dispersed nano-TiB2 particles inside the grains and rod-like nano-Si precipitates inside the cells. Both nano-TiB2 particles and nano-Si precipitates exhibited a highly coherent interface with the Al matrix, indicative of a strong interfacial bonding. The formation of this microstructure was attributed to the sequential solidification of non-equilibrium and eutectic Al-Si upon rapid cooling during SLM. As a result, the SLMed NTD-Al showed a very high ultimate tensile strength ∼530 MPa, excellent ductility ∼15.5% and high microhardness ∼191 HV0.3, which were higher than most conventionally fabricated wrought and tempered Al alloys, previously SLMed Al-Si alloys and nano-grained 7075 Al. The underlying mechanisms for this strength and ductility enhancement were discussed and a correlation between this novel microstructure and the superior mechanical properties was established. This study provides new and deep insights into the fabrication of metal matrix nanocomposites by SLM from in-situ pre-decorated composite powder. Graphical abstract: Image 1